Activation studies of a PET cyclotron bunker. (August 2019) - Vichi, S.; Zagni, F.; Cicoria, G.; Infantino, A.; Riga, S.; Zeller, M.; Carzaniga, T.S.; Nesteruk, K.P.; Braccini, S.; Marengo, M.; Mostacci, D.
Abstract: During the operational life of a PET Cyclotron, the concrete walls of its vault are activated by secondary neutrons. For this reason when considering dismantling of such accelerators, a considerable amount of low level solid radioactive waste has to be characterized and disposed. To decrease future dismantling costs, the amount of radioactive waste has to be evaluated in advance to define an optimum decommissioning strategy. Aim of this work is to develop methodologies for the preliminary assessment of activation induced in a bunker via experimental measurements. Two different facilities were studied and different approaches were adopted: non-destructive, in field measurements using a portable CZT detector were performed in the bunker of a 16.5 MeV GE PETtrace (S. Orsola-Malpighi Hospital of Bologna); while core drilling samples were extracted from the bunker of an 18 MeV IBA Cyclone 18 H C (Inselspital in Bern) and measured in laboratory with an HPGe detector. The principal long-lived radionuclides found in concrete were Eu-152, Mn-54, Co-60, Sc-46, Cs-134 with activity concentrations comprised between 0.01 and 0.6 Bq/g. In all performed measurements the total activity concentration exceed the clearance level of Directive (2013)/59/Euratom. Considering a hypothetical decommissiong of the two facilities, the amount of low lever radioactive waste estimated was about 93 m 3 in the case of S. Orsola-Malpighi, while about 58 m 3 for Insespital facility. Both the methodologies have proved to be adequate for the purposes. Highlights: Activation assessment in PET cyclotron facilities via experimental measurements. Two different methodologies: non-destructive measurements and concrete sampling. Assessment based on the two most common PET cyclotrons. Evaluation of radioactive waste to define an optimum decommissioning strategy.